2019
DOI: 10.1332/204674317x14896713788707
|View full text |Cite
|
Sign up to set email alerts
|

‘We’re not related in any way, only by blood’: Danish sperm donors and (imagined) relationships

Abstract: Newcastle University ePrints -eprint.ncl.ac.uk Wheatley A. 'We're not related in any way, only by blood': Danish sperm donors and (imagined) relationships. Families, Relationships and Societies 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Qualitative research has shown that donors are concerned about how their own children would react when they were told that their father was a donor (Wheatley, 2019). The current study showed that almost half of the donors intended to tell but studies on disclosure show that intentions are not always put into practice (Nuffield Council on Bioethics, 2013).…”
Section: Discussionmentioning
confidence: 79%
“…Qualitative research has shown that donors are concerned about how their own children would react when they were told that their father was a donor (Wheatley, 2019). The current study showed that almost half of the donors intended to tell but studies on disclosure show that intentions are not always put into practice (Nuffield Council on Bioethics, 2013).…”
Section: Discussionmentioning
confidence: 79%
“…Within the current field of policy-making and research on donors' attitudes towards their donor offspring (e.g. Crawshaw et al 2007, Daniels et al 2012, Jadva et al 2011, Speirs 2012, Wheatley 2017, there is a widespread (and understandable) assumption that this form of connection is what really matters (for a critical engagement with such understandings, see Gilman and Nordqvist 2018). If the act of donating is a way of forming social bonds, as suggested by Shaw (2007), it is, I think, an empirical question as to how that plays out.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, as already mentioned, donors have received much less attention. The research that does exist has tended to be quantitative in nature, exploring mainly anonymous donors' motivations for donating, as well as their attitudes towards donor offspring and potential future contact with said offspring (Crawshaw et al 2007, Daniels and Lewis 1996, Daniels et al 2011, Freeman et al 2016, Jadva et al 2011, Kirkman et al 2014, Speirs 2012, Wheatley 2017; for a systematic review, see van den Broeck et al 2013). However, as pointed out by van den Broeck et al (2013), donors have not been regarded as people in their own right.…”
Section: Donating In Context and Researchmentioning
confidence: 99%
“…Non-donors have a fairly accurate picture of the situation as 38.8% thought that their partner would support their decision to donate (Provoost et al, 2018). Several donors reported that a current or past partner had objected to them becoming a donor because sperm donation created an obligation that may affect their family in the future (Wheatley, 2019). Donating sperm may put a strain on their (current or future) relationship and may lead to conflicts and negative reactions (Kalampalikis et al, 2006).…”
Section: Stigma and Attributional Parenthoodmentioning
confidence: 99%